1973
DOI: 10.1177/002188637300900409
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Effectiveness, and Organizational Development: A Field Study in R & D

Abstract: Trust and organizational development in research and development laboratories were studied, using a multiple time-series, natural quasi-experimental research design. Nine focal groups from three organizations, each with five to 10 members, participated in the project. Most individuals completed two batteries of questionnaires several months apart. Two hypotheses were supported. First, the more an individual trusts his workgroup and the more he generally trusts others with whom he interacts during his work, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 9 publications
2
25
0
3
Order By: Relevance
“…Davis et al 2000 Trust in general manager has ‫)ם(‬ effect on business-unit performance p n/a Dirks 1999 Trust within group has ‫)ם(‬ effect on group performance ns ‫12.0מ‬ to 0.20 Dirks 2000 Trust in leader has ‫)ם(‬ effect on group performance p 0. 57 Friedlander 1970 Trust within group has ‫)ם(‬ effect on group performance ns n/a Kegan and Rubenstein 1973 Trust within group has ‫)ם(‬ effect on group performance n/ns ‫13.0מ‬ to 0.30 Kimmel et al 1980 Trust between negotiators has ‫)ם(‬ effect on dyad performance ns n/a Klimoski and Karol 1976 Trust in partners has ‫)ם(‬ effect on group performance p n/a Schurr and Ozanne 1985 Trust between negotiators has ‫)ם(‬ effect on dyad performance ns/p 0.16 to 0.23 Zaheer et al 1997 Trust has ‫)ם(‬ effect on interorganizational relationship performance ns 0.26 to 0.39 Boss 1978 Trust has ‫)ם(‬ effect on sat. with meeting p 0.65 Brockner et al 1997 Trust has ‫)ם(‬ effect on sat./support for leader; relationship moderated by outcome favorability p 0.65 Driscoll 1978 Trust has ‫)ם(‬ effect on job sat.…”
Section: Individual Performancementioning
confidence: 99%
“…Davis et al 2000 Trust in general manager has ‫)ם(‬ effect on business-unit performance p n/a Dirks 1999 Trust within group has ‫)ם(‬ effect on group performance ns ‫12.0מ‬ to 0.20 Dirks 2000 Trust in leader has ‫)ם(‬ effect on group performance p 0. 57 Friedlander 1970 Trust within group has ‫)ם(‬ effect on group performance ns n/a Kegan and Rubenstein 1973 Trust within group has ‫)ם(‬ effect on group performance n/ns ‫13.0מ‬ to 0.30 Kimmel et al 1980 Trust between negotiators has ‫)ם(‬ effect on dyad performance ns n/a Klimoski and Karol 1976 Trust in partners has ‫)ם(‬ effect on group performance p n/a Schurr and Ozanne 1985 Trust between negotiators has ‫)ם(‬ effect on dyad performance ns/p 0.16 to 0.23 Zaheer et al 1997 Trust has ‫)ם(‬ effect on interorganizational relationship performance ns 0.26 to 0.39 Boss 1978 Trust has ‫)ם(‬ effect on sat. with meeting p 0.65 Brockner et al 1997 Trust has ‫)ם(‬ effect on sat./support for leader; relationship moderated by outcome favorability p 0.65 Driscoll 1978 Trust has ‫)ם(‬ effect on job sat.…”
Section: Individual Performancementioning
confidence: 99%
“…The concept of trust fits this definition of homonymy. Trust has been defined as: a behavior (e.g., Zand, 1972); an attitude (Kegan & Rubenstein, 1973); a confidence (Cohen, 1966); an expectancy (Rotter, 1980;Scanzoni, 1979); a belief or set of beliefs (Barber, 1983;Rotter, 1967); a dispositional variable (Rosenberg, 1957;Rotter, 1967Rotter, , 1980; a situational variable (Johnson-George & Swap, 1982); a structural variable (Fox, 1974;Lewis & Weigert, 1985a,b): a social agency relationship variable (Shapiro, 1987a); and, an interpersonal variable (Rempel, Holmes & Zanna, 1985). Some have discussed and described trust and its effects without specifically defining it (Granovetter, 1985).…”
Section: Problem 1--conceptual Definitionmentioning
confidence: 99%
“…The Bowers study actually reported a series of different interventions using a one-group pre-test/ post-test design for each and then compared the results of the interventions in terms of &dquo;in-common&dquo; effectiveness measures. Kegan and Rubenstein (1973) compared groups from one organization going through a complete program of organizational lab training with groups from another organization that had some experience with T-groups and with still other groups from another organizaton participating in an &dquo;OD experiment.&dquo; Bowers found morale was not improved but in fact had degenerated. Zand reported mixed results on climate measures; Kegan and Rubenstein reported improved morale, climate, profitability, and productivity in relation to the &dquo;control&dquo; group(s).…”
Section: Organization Sensitivity Trainingmentioning
confidence: 99%